CHARACTERIZATION OF IRON SAND MAGNETIC PROPERTIES DEPENDING ON THE SAND GRAIN SIZE IN LAMPANAH BEACH AND ANOI ITAM BEACH, ACEH PROVINCE - MASRURAH (NIM: 22316008), ZAKIA
Indonesia has an Iron Sand that spread off in almost all regions. The use of magnetic minerals in iron sand which can be used as a high-value products being a target for exploitation. But the mining process has caused a lot of environmental damage. One of the efforts that can be done as an effort to reduce environmental damage is to do a selective mining process, where iron sand with high magnetism and the highest deposits only are mined. This study was aim to determine the character of iron sand through the pattern of sands distribution, magnetic values and magnetic minerals content in grain size sand respevtively. For this reason, the study of magnetic properties characterization on iron sand from two different places were Lampanah Beach and Anoi Itam Beach by measuring magnetic susceptibility using the two-frequency Bartington MS2B system, and chemical testing in the form of XRF and XRD measurements has been done. But previously the iron sand was distributed first into five groups, namely very coarse sand (VCS), coarse sand (CS), medium sand (MS), fine sand (FS) and very fine sand (VFS) using a group of sieves from ASTM. There 9 samples from Lampanah Beach and 10 samples from Anoi Itam Beach were studied. Based on the results obtained, the iron sand in Lampanah Beach was dominated by the MS and FS sand grains, while on the Anoi Itam beach was dominated by the FS grain grains. Magnetic susceptibility values of iron sands in Lampanah Beach vary from 365 to 6237,5 ÃƒÂ—10−8m3kg−1where the VFS group has the highest susceptibility value while in Anoi Itam Beach varies from 556,2 to 5028,2 ÃƒÂ—10−8m3kg−1 where the MS group has the highest susceptibility value. In general at both studied area, there were an increase in magnetic susceptibility values from the coarse grain size (VCS) to the finest grain size (VFS) of iron sand. There were a significant increase in Fe elemental concentrations from the coarse grain size (VCS) to the finest grain size (VFS). There were a difference in the magnetic minerals content obtained for each sand grain size. So it can be concluded that there were differences in the characteristics of iron sand from the both beaches of study area.